Attosecond energy transfer: suppressing X-ray emission and enhancing electron production - Hofierka, Jaroslav; Cederbaum, Lorenz S. (Radiation physics and chemistry, 2026)
Energy transfer processes among atoms and molecules are widely investigated experimentally and theoretically. The usually considered range of transferred energies covers small to intermediate size energies. In this work we raise the question under what circumstances the transfer of large energies can be efficient. At such energies the transfer process leads to ionization of the environment, and is thus related to Interatomic (or Intermolecular) Coulombic Decay (ICD) much investigated for small to intermediate size energies. At the large excess energies studied here, however, relativistic effects arising from the finite speed of light become decisive and lead to substantial impact on the energy transfer. A key ingredient is the extremely short radiative lifetime of the donor, which can be in the attosecond, 10−18 s, time regime when deep (e.g., 1s) core vacancies of heavy atoms are involved. In an isolated donor, the resulting X-ray emission dominates by far the Auger (often called Auger-Meitner) decay. This is in strong contrast to the situation in lighter atoms where the radiative decay rate is often negligible compared to the Auger decay rate. It is shown that when the highly excited (or excited-ionized) heavy donor is embedded in an environment, the energy transfer can proceed on extremely fast timescales similar to those of the radiative lifetimes of the isolated donor. Consequently, the X-ray emission is, depending on the environment, partially or even nearly completely suppressed and instead electrons are produced in the environment. Consequences for the field of radiation damage are discussed.